Utility of NEWS-2 in Predicting ICU Admission from Emergency Department and Mortality Risk: A Prospective Cohort Study (Academia Journal of Medicine, 2026)
Background: The National Early Warning Score 2 (NEWS-2) is a standardized clinical tool designed to detect acute deterioration in hospitalized patients. Its utility in predicting critical outcomes directly from the emergency department (ED) remains an area of active investigation. Methods: A prospective cohort study was conducted at a tertiary care hospital over 18 months, enrolling 847 adult patients presenting to the ED. NEWS-2 scores were calculated upon arrival, and patients were followed until hospital discharge or death. Primary outcomes included ICU admission within 48 hours and 30-day in-hospital mortality. Receiver operating characteristic (ROC) curve analysis, logistic regression, and survival analysis were performed. Results: The mean age was 58.4 ± 16.7 years, with 54.3% male patients. The mean NEWS 2 score was 5.8 ± 3.4. ICU admission occurred in 127 patients (15.0%), and 30-day mortality was 8.7% (n=74). Patients requiring ICU admission had significantly higher NEWS-2 scores (9.2 ± 2.8 vs. 5.2 ± 3.1, p
Keywords: NEWS-2; emergency department; ICU admission; mortality prediction; early warning score; critical care; triage